Hubungan Pola Asuh Orang Tua Dengan Kemandirian Anak Berkebutuhan Khusus Di Sekolah SKH Caraka Pratama Kelurahan Kutajaya, Kecamatan Pasar Kemis, Kabupaten Tangerang: The Relationship Between Parenting Styles and the Independence of Children with Special Needs at SKH Caraka Pratama School Kel. Kutajaya, District. Kemis Market, Kab. Tangerang - Munajah, Siti; Mariyani (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Parents who have children with special needs must provide the right parenting style according to the child's condition; so that through the right parenting style parents can develop the child's self-confidence, ability, and independence. Formation of child independence; and parenting style play an important role when most of the child's time is spent in the family environment (home).  Methods: This research is a quantitative analytic study with a cross-sectional design. The sample in this study was children with special needs who attended SKH Caraka Pratama Kel. Kuta Jaya, Kec. Kemis Market, Kab. Tangerang, totaling 32 people with a total sampling technique. The research instrument used a questionnaire. Data is primary data analyzed using a square test.  Results: The results of the univariate analysis showed that most of the parenting styles of ABK parents were positive by 53,3%; the child's independence depended by 66,7%. The results of the bivariate analysis found that there was a significant relationship between parenting style and the independence of children with special needs with a p-value = 0,019.  Discussion: There is a significant relationship between parenting styles and the independence of children with special needs.